Modelling the influence of laser drilled recast layer thickness on the fatigue performance of CMSX-4 - Morar, Nicolau I.; Roy, Rajkumar; Gray, Simon; Nicholls, John R.; Mehnen, Jorn (Elsevier, 2018)
This paper introduces a novel approach to fatigue life prediction modelling considering the laser drilling effect on film cooling holes of turbine vanes. The methodology proposed is based on a stress-life model such as the Basquin law and the introduction of manufacturing damage effect. The proposed empirical model gives a unique versatility compared to other stress-life models by considering surface damage such as the recast layer produced by the laser drilling process. The proposed empirical model has been thoroughly tested and validated using existing fatigue data. The statistical analysis shows that the proposed model is adequate for estimating the fatigue life of laser drilled specimens considering the recast layer thicknesses effect. The proposed model also can estimate the life of untested specimens even when only a small sample of fatigue data is available, thereby reducing the required testing data.
Keywords: Fatigue life; surface defects; laser drilling; recast layer